Concomitant Rhinoplasty and Septal Perforation Repair - Kridel, Russell W.H.; Delaney, Sean W. (Facial Plastic Surgery, 2020)
The rhinoplasty surgeon may encounter nasal septal perforations (NSPs) during the examination of the prospective rhinoplasty candidate, many of whom have had prior septal surgery. While small NSPs may be asymptomatic, larger NSPs may cause nasal obstruction, crusting, bleeding, or external nasal deformities. Septal perforation repair and rhinoplasty can be safely and effectively performed simultaneously for the appropriate surgical candidate. In this article, we review the important considerations when determining the surgical candidacy for concomitant rhinoplasty and septal perforation repair.
Keywords: rhinoplasty; septal perforation; septoplasty